Legal Framework for Waqf Management in Malaysia: Towards Uniformity of Laws: (Kerangka Undang-undang Pengurusan Wakaf di Malaysia: Ke Arah Keseragaman Undang-undang) (Kanun: Jurnal Undang-undang Malaysia, 2016)
This article discusses the legal framework for waqf management in Malaysia through legal doctrinal analysis. Although the Administration of the Religion of Islam Enactments contain provisions relating to waqf, these provisions are not comprehensive in nature. Johor, Selangor, Negeri Sembilan and Melaka have introduced more detailed rules or waqf enactments. This article examines several matters which are not uniform in the state waqf laws and discusses the various mechanisms under the Federal Constitution towards uniformity of laws in the states. Efforts have been made by the Department of Islamic Development Malaysia (JAKIM) and the Department of Awqaf, Zakat and Hajj (JAWHAR) to come up with a draft federal law on waqf that is to be the model law for the states' waqf enactments. The recommendation to establish a Commission for Uniformity of Shariah Laws is an alternative to continue the work towards uniformity of waqf laws in Malaysia.Keywords: waqf, laws, Malaysia